Experimental Analysis of Energy Efficient and QoS Aware Objective Functions for RPL Algorithm in IoT Networks - ARAT, Ferhat; DEMİRCİ, Sercan (Sakarya university journal of computer and information sciences, 2021)
The Internet of Things (IoT) refers to smart devices with limited resources that connect to the Internet and transmit data. Routing is an important process in this structure, which can be described as the general frame of wireless sensor networks (WSNs). The Routing Protocol for Low-Power and Lossy Networks (RPL) is recommended by the Internet Engineering Task Force (IETF) to provide communication in resource-constrained networks and is designed for routing in IoT. Basically, it is the Internet Protocol Version 6 (IPv6) protocol developed based on the energy consumed by devices. The algorithm has an important place in the performance of the IoT network. In this paper, the performance of the RPL under different objective functions (OFs) is examined. OFs are symbolized and defined by detailed equations. This study provides an experimental analysis of the RPL algorithm. An overview of the RPL algorithm is also included. Finally, the RPL algorithm is simulated by a custom simulator which is performing on the application layer, created using the Python programming language. The algorithm’s behaviour in terms of different OFs such as throughput maximization, energy efficiency maximization and energy consumption minimization was observed and the results were evaluated under different parameters such as packet size, number of nodes and different signal-to-noise ratio (SNR) values. Our experimental results may be useful for both researchers and practitioners working in related fields.